The change of conceptions in pre-service primary teachers about contents of sciences - Ezquerra Martinez, Angel; Hamed, Soraya; Martín del Pozo, Rosa (Revista Complutense de Educación, 2016)
The aim of this article is to show the changes detected in the conceptions of future primary school teachers about science contents before and after an initial training course. The course consisted of a series of activities included in a workbook and an audiovisual; requesting the preparation of successive proposals of teaching by Teacher Training students and their corresponding reflection on what and how to teach sciences, the role of students’ ideas, teaching methodology and evaluation. In addition, school research practices were conducted and innovative schools were visited. The study was carried out with 311 second-year Primary School Teacher Training students organized in 92 working teams. The information was collected through a questionnaire (pre and post-test) and treated with multivariate techniques. The analysis of the conceptions about school contents reveals an initial majority position, which we can consider close to the inquiry-based model, but with some presence of traditional approaches. After the training course changes were observed with significant differences of varying degrees on the way to present contents to primary school students, on the different types of contents and on the selection of those contents.